Validation of biomedical processes in the Indonesian Health Survey Sungguminasa Census Block, South Sulawesi - Saleh, Muhammad; Anwar, Arif; Fitrah, Muhammad Aidil; Wahiduddin, Wahiduddin (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
The implementation of this validation aims to investigate the implementation of the field laboratory process of the 2023 Sungguminasa SKI Census Block, Gowa Regency, South Sulawesi. Biomedical process validation is an important step in ensuring sample safety and data validation of SKI 2023. This validation methodology involves observing the implementation of biomedical examinations, dental and oral health of respondents and interviews with medical personnel. The validation results show that the implementation of the biomedical process is quite smooth. The response of respondents was quite good, evidenced by the presence of 28 respondents out of 39 respondents who received informed consent. However, from the officer's side, there was non-compliance with the SOP for dental and oral health examination, such as not encouraging respondents to rinse their mouth and not using lighting according to the inspection SOP standards. This validation process also identifies several recommendations for the smooth implementation of biomedical examinations and dental and oral health, among others, the administrative process and filling out the form/file for the completeness of biomedical examinations by the enumerator team takes a long time, so there is often a time gap between respondents. Therefore, it is recommended that this filling process should be carried out before field laboratory activities begin. In addition, it is necessary to update and socialize SOPs in Dental and Oral Health examinations to local medical personnel.